Current status and future directions of T‐lymphoblastic lymphoma in children and adolescents. (15th March 2016) - Burkhardt, Birgit; Mueller, Stephanie; Khanam, Tasneem; Perkins, Sherrie L.
Summary: The main challenges in the treatment of T‐cell lymphoblastic lymphoma (T‐LBL) in children and adolescents are twofold: to increase survival rates in concert with reduction of acute and long‐term toxicities including the rate of secondary malignancies. The need for molecular and prognostic markers in T‐LBL is crucial to allow for systematic treatment optimization and may serve as targets for new treatment approaches.